Factors of Effective Class Management in Elementary School Music Teaching - Slavica D. Stefanović (University of Belgrade, Teacher Education Faculty, 2019)
This paper aims to address the success rate of music teachers who teach in elementary school and create the social environment for learning. The goal of this paper is to define, by broadening the areas of genral and music pedagogy, the factors of effective class management and their application in elementary school. Theoretical considerations are based on current and relevant scientific and professional literature and include topics and issues unique to music teaching in elementary school as well as the factors involved in the effective management of the classroom which contribute to teachers' ability to create a social environment for learning. The results of the exploratory research are presented in the empirical part of the paper. The factors of effective class management in elementary schools are described in three different contexts: school learning, social learning and socio-psychological learning, as perceived by teachers and students. The basic findings confirm the assumption that all three groups of factors have a significant role in classroom management in higher grades of elementary school. The research involved 30 music teachers from various cities in Serbia and 689 of their elementary school pupils.